Sustainability Practices in MSMEs: A Quantitative Analysis of the Impact of Green Supply Chain Management, Consumer Awareness, and Regulatory Compliance on Market Performance - Purwoko Purwoko; Loso Judijanto; Zainal Abidin; Sella Antesty (Westscience Press, 2023)
This research looks into the intricate connections that exist between market performance, customer awareness, regulatory compliance, and sustainable practices among Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia. A varied sample of 350 business owners was used in the study, with consideration given to factors such as age, geography, expertise in the industry, and size of the business. The study investigated the relationship between Green Supply Chain Management (GSCM) practices, customer awareness, regulatory compliance, and market performance through rigorous statistical analysis. The findings demonstrate a strong and positive correlation, underscoring the significance of sustainable business practices for MSMEs doing business in Indonesia. For practitioners and policymakers seeking to promote environmentally conscious corporate practices and enhance MSME sector competitiveness in the marketplace, this study offers insightful information.